2011
DOI: 10.1182/blood-2010-08-302729
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing the potential for AAV vector genotoxicity in a murine model

Abstract: IntroductionLiver-directed gene transfer using adeno-associated virus (AAV) vectors has the potential to serve as therapy for several inherited hematologic diseases. One such disease is the bleeding disorder hemophilia B, caused by a deficiency in coagulation factor IX (FIX). Currently, there are 2 clinical trials for hemophilia B that use liver-directed AAV-mediated gene transfer of the F9 gene (www. clinicaltrials.gov; identifiers NCT00515710 and NCT00979238). One of these trials reported transient efficacio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
181
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(192 citation statements)
references
References 50 publications
6
181
3
2
Order By: Relevance
“…45 A second, relatively large study, involving 132 mice, specifically designed to address the issue of HCC following intravenous administration of rAAV vectors, showed no statistically significant increase in HCC in mice injected with an rAAV vector encoding clotting factor IX. 46 However, the small number of HCCs observed in this study, five in total, four of which occurred in the rAAV-treated group, may not have been sufficient to detect a significant association. Nevertheless, this study also used integration profiling and gene expression analysis to demonstrate that the HCCs appeared free of clonal integration events, or gene expression changes related to rAAV integration.…”
Section: Aav and Hcc: An Overview Of Published Studiesmentioning
confidence: 49%
See 2 more Smart Citations
“…45 A second, relatively large study, involving 132 mice, specifically designed to address the issue of HCC following intravenous administration of rAAV vectors, showed no statistically significant increase in HCC in mice injected with an rAAV vector encoding clotting factor IX. 46 However, the small number of HCCs observed in this study, five in total, four of which occurred in the rAAV-treated group, may not have been sufficient to detect a significant association. Nevertheless, this study also used integration profiling and gene expression analysis to demonstrate that the HCCs appeared free of clonal integration events, or gene expression changes related to rAAV integration.…”
Section: Aav and Hcc: An Overview Of Published Studiesmentioning
confidence: 49%
“…Donsante et al injected the mice on postnatal day (PND) 1-2; Bell et al and Li et al injected young adult animals. 39,45,46 These data suggest that mice injected during the newborn period may be more susceptible to the development of rAAV-associated HCC and, furthermore, that the HCC association was not mouse model dependent.…”
Section: Aav and Hcc: An Overview Of Published Studiesmentioning
confidence: 69%
See 1 more Smart Citation
“…Although insertion of an entire promoter/enhancer would be an unusual type of spontaneous mutation, epigenetic dysregulation could have produced the human tumors, because we observed reduced cytosine methylation within a CpG island adjacent to the syntenic insertion site in some C3 HCCs. Furthermore, our findings raise the possibility that unintended vector integration at the human locus might also lead to C3 HCC in gene therapy trials, despite numerous preclinical studies demonstrating safety in other animal models (8)(9)(10)43).…”
Section: Discussionmentioning
confidence: 72%
“…A later study of sleeping beauty transposition also found HCCs with integrations at this locus (7). Both studies highlight the potential genotoxicity of vector integration in hepatocytes, but their significance remains controversial because other reports have shown that animals do not develop HCC after AAV vector injections (8)(9)(10). The integration site locus contains a complex set of imprinted genes that are uniquely dysregulated after reprogramming to pluripotency (11), and two noncoding RNAs (Rian and Mirg) that contain multiple snoRNAs and microRNAs (12).…”
mentioning
confidence: 98%